Japanese Cedar (Cryptomeria japonica) Pollinosis in Jeju, Korea: Is It Increasing? - Lee, Jaechun (Allergy Asthma Immunol Res, 2015)
Jeju is an island in South Korea located in a temperate climate zone. The Japanese cedar tree (JC) has become the dominant tree species while used widely to provide a windbreak for the tangerine orchard industry. An increase in pollen counts precedes atopic sensitization to pollen and pollinosis, but JC pollinosis in Jeju has never been studied. We investigated JC pollen counts, sensitization to JC pollen, and JC pollinosis. Participants were recruited among schoolchildren residing in Jeju City, the northern region (NR) and Seogwipo City, the southern region (SR) of the island. The JC pollen counts were monitored. Sensitization rates to common aeroallergens were evaluated by skin prick tests. Symptoms of pollinosis were surveyed. Among 1,225 schoolchildren (49.6% boys, median age 13 years), 566 (46.2%) were atopic. The rate of sensitization to Dermatophagoides pteronyssinus (35.8%) was highest, followed by D. farinae (26.2%), and JC pollen (17.6%). In the SR, 156 children (23.8%) were sensitized to JC pollen; this rate was significantly higher than that in the NR (59 children, 10.4%, P<0.001). A significant increment in the sensitization rate for JC pollen with increasing school level was observed only in the SR. JC pollen season in the SR started earlier and lasted longer than that in the NR. JC pollen season in Jeju was defined as extending from late January to mid-April. The prevalence of JC pollinosis was estimated to be 8.5%. The prevalence differed significantly between the NR and SR (5.3% vs 11.3%, P<0.001), mainly due to the difference in sensitization rates. JC pollen is the major outdoor allergen for early spring pollinosis in Jeju. JC pollen season is from late January to mid-April. Warmer weather during the flowering season scatters more JC pollen in the atmosphere, resulting in a higher sensitization rate in atopic individuals and, consequently, making JC pollinosis more prevalent.